Еквівалентна рекурентна формула для узагальненого квазідиференціального рівняння та її застосування - Тацій, Р.М.; Власій, О.О. (Видавничий дім "Академперіодика" НАН України, 2007)
The equivalence of an (n+m)-order generalized quasi-diferential equation and an (n+m)-order difference equation which will be named by the equivalent recurrent formula is established. Applications of the equivalent recurrent formula are considered.